2018
DOI: 10.1097/mpg.0000000000001974
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Suspected Nonalcoholic Fatty Liver Disease in Lean Adolescents in the United States

Abstract: The estimated prevalence of suspected NAFLD among lean adolescents in the US was found to be 8% with evidence of metabolic derangements such as low HDL, hypertriglyceridemia, and IR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…NAFLD also occurs in children without obesity. In a nationally representative sample of adolescents with normal body mass index percentile, 8% had unexplained liver chemistry elevation that was interpreted as suspected NAFLD 12 …”
Section: Risk Factors For Nafld In Childrenmentioning
confidence: 99%
“…NAFLD also occurs in children without obesity. In a nationally representative sample of adolescents with normal body mass index percentile, 8% had unexplained liver chemistry elevation that was interpreted as suspected NAFLD 12 …”
Section: Risk Factors For Nafld In Childrenmentioning
confidence: 99%
“…Recent data have shown that normal body weight does not protect from the development of NAFLD and it can also occur in non-obese individuals [73,74]. The incidence of lean NAFLD in adolescents ranging from 8% in the USA to 16% in the Asia-Pacific region [75]. According to MAFLD criteria, we are able to diagnose it also in non-overweight and non-obese patients, when we confirm a presence of liver steatosis with at least two mentioned above metabolic risk abnormalities.…”
Section: From Nafld To Mafldmentioning
confidence: 99%
“…The largest epidemiological study on lean NAFLD in Caucasian adults in the USA analyzed the data of the National Health and Nutrition Examination Survey III (NHANES III) and reported a prevalence of 7.4% for ultrasonography‐detected hepatic steatosis in non‐obese cases (BMI < 25 kg/m 2 ), which was substantially lower compared with 27.7% in overweight/obese subjects 21 . Furthermore, a recent cross‐sectional study on adolescents showed that suspected lean NAFLD could be a threat to all age groups 22 . Data from 1482 lean individuals (BMI less than 85th percentile) aged between 12 and 18 years, who were enrolled in the NHANES during the 2005 to 2014 cycles, found that 8% of the subjects were suspected of NAFLD (defined by alanine aminotransferase [ALT] > 22.1 U/L for girls and > 25.8 U/L for boys) 22 .…”
Section: Prevalencementioning
confidence: 99%
“…Furthermore, a recent cross‐sectional study on adolescents showed that suspected lean NAFLD could be a threat to all age groups 22 . Data from 1482 lean individuals (BMI less than 85th percentile) aged between 12 and 18 years, who were enrolled in the NHANES during the 2005 to 2014 cycles, found that 8% of the subjects were suspected of NAFLD (defined by alanine aminotransferase [ALT] > 22.1 U/L for girls and > 25.8 U/L for boys) 22 . They also reported a higher rate of hypertriglyceridemia, insulin resistance (IR), and low high‐density lipoprotein among lean NAFLD patients compared with their non‐NAFLD counterparts 22 …”
Section: Prevalencementioning
confidence: 99%